Correlation of mature mean follicle on transvaginal ultrasound and serum estradiol levels on day of trigger injection of ovulation in ovarian stimulation cycle of in vitro fertilization with retrieved oocytes - Kapoor, Avnika; Sharma, Garima; Bakshi, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Controlled ovarian hyperstimulation aims to obtain mature follicles. The present study was conducted to assess the correlation of mature follicle in transvaginal ultrasound scanning (TVS) and serum estradiol levels on day of trigger injection in ovarian stimulation cycle for IVF with the oocyte yield. Methods: In this prospective study, we evaluated oocyte donor 19 to 45 years of age who underwent oocyte retrieval at our clinic. Outcome variables like number of mature follicles visualized on TVS on the last day of stimulation was noted for all patients. On the same day, serum estradiol levels and number of mature follicles seen on TVS were noted and correlated with the number of oocytes retrieved. Ultrasound guided transvaginal oocyte retrieval was performed and total number of oocytes were noted. Results: During the study period, 20 oocytes donors were included. Mean age of the patients was 27.9±4.7 years. Mean BMI was 26.8±2.3 kg/m2. Mean FSH level was 6.89±1.79 IU/L and mean antral follicle count on day 3 was 14.06±3.56. On the day of trigger, mean mature follicle count seen on TVS was 20.4±13.8, ranging from 8 to 50. On an average, 17.2 oocytes were retrieved. On the day of trigger, mean estradiol level was 4970±203, ranging from 500 to 15,665 pg/ml. It was observed that the number of retrieved oocytes correlated significantly with the serum estradiol levels, (Pearson’s coefficient 0.94, p value<0.001) and number of mature follicles seen on TVS ((Pearson’s coefficient 0.92, p value<0.001). Conclusions: Number of retrieved oocytes correlated significantly with the serum estradiol levels and number of mature follicles seen on TVS on the day of trigger.